The Effect of Realistic Mathematics Learning Model on Mathematical Problem Solving Ability and Learning Independence of Grade VIII MTs PAB 2 Sampali Medan Students - Matondang, Nur Halimah; Syahputra, Edi; Ahyaningsih, Faiz (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
Effective mathematics learning plays an important role in improving the quality of education and human resources. However, many students have difficulty understanding mathematical concepts, especially in mathematical problem solving and learning independence. This study aims to analyze the influence of realistic mathematics learning models on the mathematical problem solving ability and learning independence of grade VIII students at MTs PAB 2 Sampali Medan. The research method used is quasi-experiment with a pretest-posttest control group design. The research sample consists of two classes, namely an experimental class that uses a realistic mathematics learning model and a control class that uses conventional methods.  Data analysis using two-track ANAVA shows that the realistic mathematics learning model has a significant influence on improving students' mathematical problem solving ability (sig. = 0.034 < 0.05) and students' learning independence (sig. = 0.000 < 0.05). However, the results of the study also showed that there was no interaction between the learning model and students' initial mathematical ability on problem solving ability (sig. = 0.627 > 0.05) or on students' learning independence (sig. = 0.994 > 0.05).   These findings indicate that the realistic mathematics learning model is effective in improving students' problem solving ability and learning independence without being affected by their initial ability level. By connecting mathematical concepts with real-life experiences, this model can help students better understand the material and become more independent in learning. Therefore, a realistic mathematics learning model is recommended as a strategy in improving the quality of mathematics learning in schools.